PEMETAAN SEBARAN TINGKAT KESEHATAN TANAMAN KELAPA SAWIT DI KABUPATEN SAMBAS MENGGUNAKAN SISTEM INFORMASI GEOGRAFIS DAN CITRA SATELIT - Sunardi Sunardi; Sudirman Masara’T; Heriyansah Heriyansah; Sangkala Sangkala; Dian Sari (JURNAL AGROTROPIKA, 2026)
The demand for palm oil commodities from Indonesia increases every year, making it very influential on the international market.  Despite its very significant contribution to the national economy, oil palm plantations face complex challenges, such as issues of land degradation, destruction of biodiversity, deforestation, and several other environmental issues. Inaccurate oil palm maintenance data which still relies on traditional methods based on historical data and field observations often requires a lot of time and costs, especially due to changes in climate conditions and pest and disease attacks. This research aims to produce a map of palm oil health conditions that can be used for more efficient production management by optimizing quality and quantity. This research was carried out in May-December 2025 in Sambas district spread across 10 sub-districts (Sambas, Sejangkung, Sebawi, Semparuk, Selakau, Subah, Tebas, Sajad, Galing, and Sajingan) using field observation methods and analyzing satellite image data and geographic information systems integrated with soil laboratory analysis data (content of essential nutrients in the soil). The satellite image data used is image data recorded by Landsat 8 OLI in 2025 which was processed using Quantum GIS software, the Indonesian Earth Map (RBI), and the land use map of Sambas district. The research results showed that there were variations in soil nutrient content concentrations and NDVI values ​​which correlated with the health level of oil palm plants with an average range of 0.0202 – 0.4351 (high health level).